Upaya Menumbuhkan Kesadaran Masyarakat Dalam Menjaga Kebersihan Lingkungan Sungai Dengan Aksi Membersihkan Sungai - Umi Nur Solikah; Libria Widiastuti; Veronika Veronika; Tirta Mas Silih Wangi; Sofia Amisha Hafizah (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Environmental cleanliness is one of the benchmarks of the quality of life of the community. A clean environment is everyone's dream. But it is not easy to create our environment can look clean and tidy so that it is comfortable to look at. Many slogans invite us to maintain cleanliness and safety. But in reality, we still litter. This community service is a work program of KKN Islamic University of Batik Surakarta in collaboration with Banaran Village, Grogol District, Sukoharjo Regency. Community service is carried out by doing social service work through river cleaning activities. The purpose of this social service activity is expected to motivate the community to be more concerned about maintaining environmental cleanliness so that the environment becomes clean and the community can avoid various diseases.